Seasonal habitat use of yellow perch Perca flavescens in a north‐temperate lake - Levi M. Feucht; Logan W. Sikora; Gabrielle P. Shay; Greg G. Sass; Joseph T. Mrnak (Aquaculture, Fish and Fisheries, 2023)
Abstract Knowledge of species‐specific fish biology, ecology, and habitat use is critical for informing science‐based management. Yellow perch Perca flavescens are an ecologically and recreationally important fish species. Yet, for many north‐temperate systems (e.g. inland lakes of Wisconsin), little is known about yellow perch seasonal habitat use and ecology. We characterised yellow perch seasonal spatial distribution, size–structure, and condition between littoral and pelagic habitats in Crystal Lake (Vilas Co., WI) during the open water period of 2021. Seasonal spatial distribution and population size–structure were characterised by contemporaneous sampling in littoral and pelagic habitats using mini‐fyke nets and vertical gill nets, respectively. Relative abundance estimates for yellow perch in the littoral zone were greatest during early spring and declined throughout the open water season. Yellow perch pelagic relative abundance estimates were lowest in spring, peaked at the onset of stratification, and then declined and remained relatively consistent throughout the open water season. In general, yellow perch population size–structure and condition were greatest in the pelagic zone. Our findings suggest that after spring spawning, larger yellow perch prefer/select pelagic habitats, while sub‐adults and juveniles prefer/select littoral habitats, potentially resulting from increased predator refugia and(or) resource availability. Our results emphasise the importance of evaluating gear and fishery assessment bias, particularly when the target species may use a range of habitat types within a system.